Does Government Ownership impact on Corporate Social Responsibility Disclosure? Case in Viet Nam - Hang Thi Thuy Pham; Jung-Sung Chang; Su-Yol Lee (My University, 2019)
Does Government Ownership impact on Corporate Social Responsibility Disclosure? Case in Viet Nam
Keywords: Government ownership; CSR disclosure; Vietnam